Pengaruh Carbon Emission Disclosure, Eco-Efficiency, dan Environmental Cost terhadap Nilai Perusahaan: Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2020–2024 - Putri, Selfi Andina; Pebriyani, Dewi (Jurnal Eksplorasi Akuntansi, 2025)
This study aims to analyze the effect of carbon emission disclosure, eco-efficiency, and environmental cost on firm value. The type of research used is quantitative research with secondary data, in the form of financial reports, annual reports, and sustainability reports obtained from the official website of the Indonesia Stock Exchange. The population used consists of companies listed on the Indonesia Stock Exchange during the period 2020–2024. The sampling method used is purposive sampling, resulting in 220 samples comprising 44 companies. Data analysis techniques utilize panel data regression analysis using Eviews 12 software. The research findings indicate that carbon emission disclosure, eco-efficiency, and environmental costs do not influence firm value.